Campus Canopy, 1935-10-11 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1935)
Artist Series Will Bring Halliburton Here Monday Night -- New Members Chosen For Sock and Buskin -- Chancellor Pleased With Plans Of New Dormitory Upon Campus Of College Here -- Editors of Student Publications Will Attend Convention -- Hollywood Artist is Friend of Head of Woman's College -- Glee Club's Double Trio is Selected; Operetta Planned -- Philharmonic Club Tryouts Completed -- Matilda Tillman is Chosen Junior Head
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals